Implementation of Complete Systematic Land Registration Program in the City or District Of Ex-Residency Besuki (Study on the Implementation of Complete Systematic Land Registration Program in 2017 until 2019) - Faqih Sunni S.; Tunggul Anshari SN.; Supriyadi Supriyadi (Budapest International Research and Critics University, 2021)
Land has a very important role important in human life, because land is always closely related to the scope of everyday society, whether it is used for housing, farming, or conducting business activities. The existence of land has a dual function, namely as a capital asset and social asset. Therefore, to provide comfort and security to the owners and rulers of a field of land, legal land registration is very important to be carried out by the community. Thus, to make it easier for the community to obtain legal certainty, the ATR / BPN (Agrarian and Spatial Planning / National Land Agency) Institution established a program called Complete Systematic Land Registration (PTSL) which is carried out simultaneously throughout Indonesia. This study will discuss how the implementation of the Complete Systematic Land Registration Program (PTSL) in 4 (four) Ex-Residency Besuki Districts. By using an empirical juridical approach to study the applicable legal provisions and what happens in the reality of society, then it is analyzed using SWOT analysis and the effectiveness theory approach according to Soerjono Soekanto, who argues that the effectiveness of a law is determined by 5 factors, namely, law enforcers (those who apply the law) means and facilities that support law enforcement, society, and community culture. Data collection techniques used interviews and documentation. The results showed that the implementation of PTSL in 4 (four) Districts of the Former Residency of Besuki was effective in terms of law factors and facilities and infrastructure that support law enforcement. The implementation of PTSL in 4 (four) Ex-Besuki Districts was less effective in terms of Law Enforcement Factors, Community Factors, and Cultural Factors.